Climate risk management in river-based tilapia cage culture in northern Thailand - Phimphakan Lebel (2018)
© 2015, Emerald Group Publishing Limited. Purpose – The purpose of this paper is to analyse how fish farmers manage climate-related risks and explore possible ways to strengthen risk management under current and future climate. Design/methodology/approach – In total, 662 fish farmers in sites across Northern Thailand were interviewed about risks to the profitability of their fish farms and ways such risks were managed. Nonlinear canonical correlation analysis was used to relate risk factors to management practices at farm and river levels. In total, 68 in-depth interviews with farmers and other stakeholders provided additional information on climate risk management practices. Findings – Farmers use a combination of adjustments to rearing practices, cropping calendars and financial and social measures to manage those risks, which they perceive as being manageable. Many risks are season, river and place specific; implying that the risk profiles of individual farms can vary substantially. Individual risks are often addressed through multiple practices and strategies; conversely, a particular management practice can have a bearing on several different risks. Farmers recognize that risks must be managed at farm and higher spatial and administrative scales. Social relations and information play critical roles in managing these complex combinations of risks. Originality/value – This is one of the first papers to report in detail on how inland fish farmers manage climate-related risks. It underlines the need to consider multiple spatial and temporal scales and that farmers do not manage individual climate-related risks in isolation from other risks.